PENGARUH LATIHAN PLYOMETRIC TERHADAP KEMAMPUAN LAY-UP PERMAINAN BOLA BASKET DI KLUB UNO BASKETBALL - Dwi Prasetyo, oktavian; Putra, Ikhsan Maulana; wulandari, titis; Al-Ihsan, M.iqbal; Yuliana, Chindi (STKIP Muhammadiyah Kuningan, 2024)
This research aims to reveal the influence of Plyometric training on basketball lay-up ability with plyometric training. This research method is experimental research because this research requires treatment. The treatment is carried out on the independent variable and the results are seen on the dependent variable. The design used in this research is One Group Pretest Posttest Design. The exercise frequency used is 3 times a week. The length of training is 16 meetings over 5 weeks. The population in this study was the Basketball Uno Basketball club with a total of 35 people. The sampling technique uses purposive sampling, namely determining samples based on characteristics. The sample chosen was 15 players from the Basketball Uno Basketball club. From the results of data analysis, a sig value of 0.000 (sig < 0.05) was obtained, which shows that there is an influence of Plyometric training on the basketball lay-up ability of the Basketball Uno Basketball club, in other words that there is an influence of Plyometric training on basketball playing ability.